2018
DOI: 10.3897/subtbiol.27.28909
|View full text |Cite
|
Sign up to set email alerts
|

Day–night and seasonal variations of a subterranean invertebrate community in the twilight zone

Abstract: Being characterized by the absence of light and a reduced environmental cyclicity, the subterranean domain is generally regarded as temporally stable. Yet, in the proximity of cave entrances (twilight zones), patterns of sunlight and darkness can be detected within the 24-hour day–night cycle. In parallel, changes in the abiotic and biotic conditions are expected; however, these patterns have been rarely explored in animal communities dwelling in the twilight zone. We performed a biological investigation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 83 publications
1
24
0
1
Order By: Relevance
“…Subterranean habitats are suitable for studying species interactions, ecological niches, and temporal and spatial patterns in terrestrial subterranean communities. However, subterranean communities as a whole are only rarely considered in relation with environmental conditions (e.g., Bento et al, ; Di Russo et al, ; Mammola & Isaia, ; Mammola et al, ; Pipan et al, ; Sendra & Reboleira, ; Tobin et al, ). Consequently, community responses to environmental conditions are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Subterranean habitats are suitable for studying species interactions, ecological niches, and temporal and spatial patterns in terrestrial subterranean communities. However, subterranean communities as a whole are only rarely considered in relation with environmental conditions (e.g., Bento et al, ; Di Russo et al, ; Mammola & Isaia, ; Mammola et al, ; Pipan et al, ; Sendra & Reboleira, ; Tobin et al, ). Consequently, community responses to environmental conditions are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the PERMANOVA clearly showed that there were no annual changes in the community composition within the three different zones in which the study cave was subdivided, i.e., the twilight, dark, and deep zones. This finding is of particular interest when considering that the transitional twilight zone analyzed in this study was in connection to the exterior environment through a large entrance and therefore, highly subject to abrupt and unpredictable seasonal and even daily climatic variations [6].…”
Section: Discussionmentioning
confidence: 84%
“…In subterranean habitats, air temperature and relative humidity display buffered seasonal variations. Solar radiation is completely absent in deep areas, yet still present but dimmed in the twilight ecotone zone [4][5][6]. In addition, subterranean environments are often energy limited in the sense that, in absence of primary producers, the main organic supply is derived from organisms living in surrounding surface habitats [1].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, environmental stability is one of the main "attractors" for populations that may come and colonize these environments, ceasing the selection of characteristics that can be advantageous under the great unpredictability of the surface environment 15 . Considering the cave environment, organisms can, for example, adapt their distributions according to uctuations in temperature or relative humidity, which are much less pronounced than in the external environments 44,45 . Regarding the environmental stability in the external habitats, climatic oscillations on the surface can extinguish epigean populations, while hypogean populations can be spared, resulting in their isolation 30,31 .…”
Section: Discussionmentioning
confidence: 99%